2017
DOI: 10.1071/wf16162
|View full text |Cite
|
Sign up to set email alerts
|

Studying interregional wildland fire engine assignments for large fire suppression

Abstract: One crucial component of large fire response in the United States (US) is the sharing of wildland firefighting resources between regions: resources from regions experiencing low fire activity supplement resources in regions experiencing high fire activity. An important step towards improving the efficiency of resource sharing and related policies is to develop a better understanding of current assignment patterns. In this paper we examine the set of interregional wildland fire engine assignments for incidents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Further, resource movement and prepositioning is an important consideration for efficiency questions. A growing body of research has helped build a foundation of knowledge in this area (e.g., [17,18,[50][51][52]); however, there is still much to be learned for the wide variety of resource types and agencies at play in the national response arena. Finally, imposing restrictions on resource use in an interagency realm is fraught with challenges, particularly given different agency priorities with respect to fire management policy, values at risk, and relative appetite for beneficial fire opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Further, resource movement and prepositioning is an important consideration for efficiency questions. A growing body of research has helped build a foundation of knowledge in this area (e.g., [17,18,[50][51][52]); however, there is still much to be learned for the wide variety of resource types and agencies at play in the national response arena. Finally, imposing restrictions on resource use in an interagency realm is fraught with challenges, particularly given different agency priorities with respect to fire management policy, values at risk, and relative appetite for beneficial fire opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…A suppression problem definition suggests that operational activities under the command organisational structure of ICS are the dominant focus in wildfire response. Further, alternatives to address suppression as a problem have focused on modelling, monitoring, decision tools and influences associated with the operational aspects of fire management (Thompson 2014;Hand et al 2015;O'Connor et al 2016;Thompson et al 2016a;Belval et al 2017;Hand et al 2107;Jolly and Freeborn 2017;Katuwal et al 2017;Wei et al 2017). Suppression has also been recognised as part of a broader operational toolbox, which includes managed wildland fire and prescribed fire.…”
Section: What Do We Mean By Wildfire Response? Operational Vs Systemsmentioning
confidence: 99%
“…Suppression has also been recognised as part of a broader operational toolbox, which includes managed wildland fire and prescribed fire. Each of these strategic approaches are recognised to have relative advantages and disadvantages in given settings (Steelman and McCaffrey 2011;Katuwal et al 2016;Belval et al 2017;Hand et al 2017;Ingalsbee 2017;Katuwal et al 2017;Stonesifer et al 2017;Wei et al 2017), including cost implications (Donovan and Brown 2005;Canton-Thompson et al 2008). The point is that there is an organisational and expertise-based path dependence based on how the problem is defined.…”
Section: What Do We Mean By Wildfire Response? Operational Vs Systemsmentioning
confidence: 99%
“…Other studies have shown ROSS to be a valuable source of information for examining dispatching and assignments for fire responders and equipment (e.g. Calkin et al 2014;Belval et al 2017;Lyon et al 2017). We only examined filled requests for IHCs; this model is not meant to be used to prioritise which requests should be filled, but rather to fill those already determined to be a priority.…”
Section: Historical Request Assignment and Availability Data Used Fomentioning
confidence: 99%